2010
DOI: 10.1080/02680510903482132
|View full text |Cite
|
Sign up to set email alerts
|

The four ‘R’s of openness and ALMS analysis: frameworks for open educational resources

Abstract: A significant movement in education concerns the use of open educational resources. By -open‖ it is generally meant that the resource is available at no cost to others for adaptation and reuse in different contexts. However -open‖ is not a simple dichotomy; rather, there is a continuum of openness. We discuss four separate aspects of reuse and demonstrate how these describe different levels of openness. We discuss how the licensing and technical aspects of open educational resources affect the relative opennes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
128
0
32

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(161 citation statements)
references
References 5 publications
1
128
0
32
Order By: Relevance
“…There have been many definitions of OER; I provide four here. Other scholars have also defined OER as teaching, learning, and research resources with intellectual property licenses that permit them to be reused, reworked, remixed, and redistributed (D'Antoni, 2009;Hilton, Wiley, Stein, & Johnson, 2009;Plotkin, 2010;Wiley, 2009). They observed that some conditions may be placed on the use of OER, such as the provision of attribution, but all OER are accessible to anyone.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…There have been many definitions of OER; I provide four here. Other scholars have also defined OER as teaching, learning, and research resources with intellectual property licenses that permit them to be reused, reworked, remixed, and redistributed (D'Antoni, 2009;Hilton, Wiley, Stein, & Johnson, 2009;Plotkin, 2010;Wiley, 2009). They observed that some conditions may be placed on the use of OER, such as the provision of attribution, but all OER are accessible to anyone.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…OERs are defined as teaching, learning, and research resources with an intellectual property license that permits them to be reused, reworked, remixed, and redistributed (D'Antoni, 2009;Hilton, Wiley, Stein, & Johnson, 2009;Plotkin, 2010;Wiley, 2009). Some conditions may be placed on the use of OERs, such as the provision of attribution, but all OERs are accessible to anyone.…”
mentioning
confidence: 99%
“…Ideally, the games should fit on the requirement of the Open Education Resources movement's "4 Rs": reuse, redistribute, revise, remix [12]. In this way, the investment is better protected against future changes, the community benefits fro m previous works and the costs can be driven down.…”
Section: Game Authoring and Modificationmentioning
confidence: 99%